'It's not a diet, it's a lifestyle': a longitudinal, data-prompted interview study of weight loss maintenance. Issue 8 (3rd August 2019) - Kwasnicka, Dominika; Dombrowski, Stephan U.; White, Martin; Sniehotta, Falko F.
Abstract: Objective: To advance understanding of the individual and environmental factors underpinning weight loss maintenance.Design: Semi-structured, data-prompted interviews were conducted with twelve overweight adult participants (three men, nine women) who had lost over 5% of their body weight in the year before baseline. Participants gathered daily data through wireless scales, activity monitors (Fitbit™), ecological momentary assessment and experience sampling (taking photographs, writing notes). They were interviewed at 3- and 6-months post baseline. Interview stimuli included personal data of weight and activity graphs, correlations of psychological factors, and self-generated notes and photographs. Interview data were analysed using the Framework Method, applying pre-specified maintenance-relevant theoretical themes.Results: The theoretical Framework provided a good fit for the narratives, with five main themes underpinning successful weight loss maintenance: sustained motivation, effective self-regulation, plentiful resources, habit formation and a supportive environment. Additionally, participants reported an identity shift from being a dieter to accepting a new healthy lifestyle. Goal prioritising and allowing for occasional controlled lapses enhanced weight loss maintenance.Conclusions: This study successfully used the novel method of data-prompted interviews to explore weight loss maintenance experiences with new explanations emerging from the data. Future research should further develop behaviour change maintenance theory and data-prompted interview method.